Influence of the geometrical and physical properties of filler in the filler–bitumen interaction. (1st February 2015) - Antunes, V.; Freire, A.C.; Quaresma, L.; Micaelo, R.
Highlights: Hydraulic and hydrated limes are composed of granulous-shaped particles. Cement and natural filler particles are mostly angular with smooth to rough surfaces. The Rigden voids of hydrated lime are much larger than those of the other fillers. The RV, the PA and the ΔTR&B test results show a strong inter-relation. It is proposed the inclusion of the f / b max ratio in filler specifications. Abstract: The objective of this laboratory study is to investigate the relationship between the geometrical and physical properties of filler and the consistency of filler–bitumen mixtures and the stripping resistance. Five fillers (3 manufactured and 2 natural) were geometrically and physically characterized with various test methods, including SEM imaging. The filler–bitumen interaction was assessed with two consistency-related mastic tests and a water susceptibility test. SEM images show significant differences in size, shape and surface texture between tested fillers, and a strong correlation with the stiffening effect. It is proposed the inclusion of the f / b max ratio, obtained from the absorbing capacity test, in the filler specifications to serve as an indicative threshold value of the filler content added.